Reutilização do resíduo cerâmico oriundo do Polo Oleiro de Iranduba e Manacapuru para emprego como elemento constituinte de base e sub-base de pavimento - (:unkn) unknown (Universidade Federal do Amazonas, 2016)
The complex of industrial manufacturing of bricks in the cities of Iranduba and Manacapuru in Amazonas state currently has about thirty ceramics industries operating with approximate daily production of 4500 tons of bricks, roof tiles and ceramic blocks, of which approximately 95% providing to Manaus demand, generating income, cause thousands of direct and indirect jobs according to the Associação dos Ceramistas do Amazonas - ACERAM. This industrial sector generates approximately 135 tons of ceramic waste (RC) at the same period due to incorrect burning, failure in the production process, poor conformation of parts among others. The purpose of this research is to evaluate the mechanical behavior of Manaus’s typical soil to stabilize it with this ceramic waste in order to apply it in layers of sub-base and pavement base and consisted of a division into two phases: the first phase were analyzed natural soil (SN) collected in the building’s construction of the Living Center at the Technology College - UFAM and the ceramic waste collected in the Indústria Cerâmica Rio Negro LTDA, located in the city of Iranduba. These materials composed the soil-residue mixing (MSR) with the following proportions: 1) MSR1: 80% SN + 20%RC; 2) MSR2: 60%SN + 40%RC; 3) MSR3: 40%SN + 60%RC e 4) MSR4: 20%SN + 80%RC. In the second phase of the research was analyzed the mixtures composed by natural soil and ceramic waste in the same proportions of the previous mixtures and increase 30% sand in the proportion of natural soil. All samples were collected, stored and prepared in accordance with the regulations to achieve the following technical tests: preliminarily, the mixtures demonstrated exceedingly plastics and with low support for enforcement purposes; then the sand (MSAR) was added as displasticizer and granulometric adjustment, subsequently analyzed its Resilience Modules by tests in the Geothechnical Laboratoy of COPPE/UFRJ. The results indicated the third composition with the addition of sand (MSAR-3) as the mixture with greater application feasibility for sub-base and pavement bases in terms of proportion and mechanical support, which again was evaluated the Resilience Module in Pavement Technology Laboratory of the Department of Transportation at the University of Polytechnic School of São Paulo - USP to confirm the data and application in a simulation of pavement’s dimensioning using the mechanistic method by computer program SisPav.

The complex of industrial manufacturing of bricks in the cities of Iranduba and Manacapuru in Amazonas state currently has about thirty ceramics industries operating with approximate daily production of 4500 tons of bricks, roof tiles and ceramic blocks, of which approximately 95% providing to Manaus demand, generating income, cause thousands of direct and indirect jobs according to the Associação dos Ceramistas do Amazonas - ACERAM. This industrial sector generates approximately 135 tons of ceramic waste (RC) at the same period due to incorrect burning, failure in the production process, poor conformation of parts among others. The purpose of this research is to evaluate the mechanical behavior of Manaus’s typical soil to stabilize it with this ceramic waste in order to apply it in layers of sub-base and pavement base and consisted of a division into two phases: the first phase were analyzed natural soil (SN) collected in the building’s construction of the Living Center at the Technology College - UFAM and the ceramic waste collected in the Indústria Cerâmica Rio Negro LTDA, located in the city of Iranduba. These materials composed the soil-residue mixing (MSR) with the following proportions: 1) MSR1: 80% SN + 20%RC; 2) MSR2: 60%SN + 40%RC; 3) MSR3: 40%SN + 60%RC e 4) MSR4: 20%SN + 80%RC. In the second phase of the research was analyzed the mixtures composed by natural soil and ceramic waste in the same proportions of the previous mixtures and increase 30% sand in the proportion of natural soil. All samples were collected, stored and prepared in accordance with the regulations to achieve the following technical tests: preliminarily, the mixtures demonstrated exceedingly plastics and with low support for enforcement purposes; then the sand (MSAR) was added as displasticizer and granulometric adjustment, subsequently analyzed its Resilience Modules by tests in the Geothechnical Laboratoy of COPPE/UFRJ. The results indicated the third composition with the addition of sand (MSAR-3) as the mixture with greater application feasibility for sub-base and pavement bases in terms of proportion and mechanical support, which again was evaluated the Resilience Module in Pavement Technology Laboratory of the Department of Transportation at the University of Polytechnic School of São Paulo - USP to confirm the data and application in a simulation of pavement’s dimensioning using the mechanistic method by computer program SisPav.
Keywords: Estabilização de solos; Estabilização de solos; Resíduo cerâmico; Resíduo cerâmico; Dimensionamento de Pavimento; Dimensionamento de Pavimento; ENGENHARIAS: ENGENHARIA CIVIL